Calcium and magnesium ion removal from water feeding a steam generator by chemical precipitation and flotation with micro and nanobubbles. Issue 17 (28th July 2020) - Silva, R. D. R.; Rodrigues, R. T.; Azevedo, A. C.; Rubio, J.
ABSTRACT: This work summarises the results of calcium and magnesium ion removal from raw water feeding an industrial steam generation system. The cations were precipitated with sodium phosphate before separation of the solids by dissolved air flotation, with micro and nanobubbles. Studies were done at bench scale and validated at pilot scale (raw water feed = 1 m 3  h −1 ; air-to-solids ratio = 0.046 mg of air mg −1 of solids; residence time = 11 min). Results indicated that chemical precipitation followed by flotation significantly improved the quality of the boiler water. Best results were obtained after precipitating the cations with 50 mg L −1 of sodium phosphate at pH 11.5 and flotation with a saturation pressure ( P sat ) of 4 bar, a recycling ratio of 30% and a sodium oleate concentration of 20 mg L −1 as an hydrophobizing reagent. The latter assisted the adhesion of the nanobubbles (100–500 nm) generated at 4 bar with a numeric concentration of about 2.5 × 10 8  NBs mL −1 . At pilot scale, the total hardness in the solution decreased by 80%; the residual calcium and phosphate ion concentrations were 12 and 2 mg L −1 respectively. This cell was designed including lamellae and perforate plate to improve the superficial loading capacity (up to 9 m h −1 ). The results were explained by chemical and interfacial phenomena and it is believed that this technique has great potential in water softening processes. GRAPHICAL ABSTRACT: UF0001